2021
DOI: 10.7759/cureus.14151
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Postoperative Analgesic Effects of the Intraperitoneal Instillation of Bupivacaine Versus Normal Saline Following Laparoscopic Cholecystectomy

Abstract: BackgroundLaparoscopic cholecystectomy is widely performed, and postoperative pain is an important factor in patient morbidity during recovery. Various modalities for postoperative pain relief have been proposed, with varying levels of success such as intravenous or intramuscular non-steroidal anti-inflammatory drugs (NSAIDs) and opioids, infiltration at the incision site with local anesthetics, intraperitoneal infiltration of local anesthetics, intraperitoneal infiltration of local anesthetics with adjuvants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Patients who were administered bupivacaine at port sites experienced lower postoperative pain and required fewer analgesic medications [ 6 ]. Several other studies have reported similar results indicating that intraperitoneal instillation reduced postoperative pain effectively [ 7 8 9 ].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Patients who were administered bupivacaine at port sites experienced lower postoperative pain and required fewer analgesic medications [ 6 ]. Several other studies have reported similar results indicating that intraperitoneal instillation reduced postoperative pain effectively [ 7 8 9 ].…”
Section: Discussionsupporting
confidence: 53%
“…In this study, NRS at 2, 4, and 10 hours were 3.3, 2.4, and 2.2. This is quite astonishing because, in many previous studies, the usual pain scale several hours after LC was about 6 to 9 without intraoperative manipulation of pain control, and with that pain level patients are usually not discharged for OPS [ 6 7 ]. NRS of the OPS group in this study was 4.5, 4.1, and 3.7 at 3, 6, and 9 hours postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main goals of intraperitoneal bupivacaine injection is to increase the drug's plasma concentration because of the peritoneum's better ability for systemic absorption. Vijayaraghavalu S. et al 23 reported an increase in plasma concentration of bupivacaine beyond the threshold value of 2mg/L following intraperitoneal administration of 50ml of 0.25% bupivacaine during laparoscopic cholecystectomy. Although substantial respiratory function decline and recurrent hypoxemia episodes (SpO92%) were found in these patients during the postoperative period, this was not the main issue.…”
Section: Figure-1mentioning
confidence: 99%
“…2,3 Following laparoscopic cholecystectomy, pain radiates from the incision site to visceral regions, 4 and shoulder tip (sub-diaphragmatic region). 5 For postoperative pain relief, various methods such as intravenous or intramuscular NSAIDs 6 and opioids, 7 infiltration at the incision site with local anaesthetics [8], intraperitoneal infiltration of local anaesthetics, 8 local anaesthetics with adjuvants, 9 and regional anaesthesia techniques such as epidurals and nerve blocks are used. All of these have varying success rates.…”
Section: Introductionmentioning
confidence: 99%